Peran Pendidikan Karakter dalam Mencegah Krisis Moral di Kalangan Generasi Muda - Putri, Mas Fierna Janvierna Lusie; Sulistiawati, Denti; Mumung, Kornelia Efriana (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
The rapid development of the era of globalization has a significant impact on various aspects of life, including the morality of the younger generation. The phenomenon of moral crisis marked by increasing deviant behavior, such as misuse of technology, promiscuity, and decreasing respect for social norms and cultural values, is a serious problem that must be addressed immediately. Amid the increasing deviant behavior and moral crisis that hit the younger generation, instilling positive characters such as honesty, responsibility, empathy, and discipline is becoming increasingly relevant. This study aims to provide information on the importance of character education in preventing moral crises among the younger generation. Character education is one of the strategic solutions and forms the personality of the younger generation to have strong moral values. The results of the study show that character education is one of the main keys in preventing moral crises and forming a generation with integrity.